Immunological characterization of an Italian PANDAS cohort - Leonardi, Lucia; Lorenzetti, Giulia; Carsetti, Rita; Piano Mortari, Eva; Guido, Cristiana Alessia; Zicari, Anna Maria; Förster-Waldl, Elisabeth; Loffredo, Lorenzo; Duse, Marzia; Spalice, Alberto (Frontiers in Pediatrics, 2024)
This cross-sectional study aimed to contribute to the definition of Pediatric Autoimmune Neuropsychiatric Disorders Associated with Streptococcal Infections (PANDAS) pathophysiology. An extensive immunological assessment has been conducted to investigate both immune defects, potentially leading to recurrent Group A β-hemolytic Streptococcus (GABHS) infections, and immune dysregulation responsible for a systemic inflammatory state. Twenty-six PANDAS patients with relapsing-remitting course of disease and 11 controls with recurrent pharyngotonsillitis were enrolled. Each subject underwent a detailed phenotypic and immunological assessment including cytokine profile. A possible correlation of immunological parameters with clinical-anamnestic data was analyzed. No inborn errors of immunity were detected in either group, using first level immunological assessments. However, a trend toward higher TNF-alpha and IL-17 levels, and lower C3 levels, was detected in the PANDAS patients compared to the control group. Maternal autoimmune diseases were described in 53.3% of PANDAS patients and neuropsychiatric symptoms other than OCD and tics were detected in 76.9% patients. ASO titer did not differ significantly between the two groups. A possible correlation between enduring inflammation (elevated serum TNF-α and IL-17) and the persistence of neuropsychiatric symptoms in PANDAS patients beyond infectious episodes needs to be addressed. Further studies with larger cohorts would be pivotal to better define the role of TNF-α and IL-17 in PANDAS pathophysiology.